Start – Up Proses Anammox Menggunakan Lumpur Telaga Kotobaru sebagai Inokulum - Putra, Randi Permana; Zulkarnaini, Zulkarnaini; Komala, Puti Sri (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2020)
ABSTRACTThe anammox process plays an essential role in removing nitrogen from the waters anaerobically. Since the discovery of anammox in 1995, no studies have reported anammox bacteria from the Indonesian environment. This research aims to begin exploring anammox bacteria from the environment in Indonesia as a tropical country. The exploration was carried out with a start-up anammox process in a continuous reactor. The reactor was constructed using a housing filter equipped with a string wound filter as a supporting media for biofilm. Sludge from Koto Baru Lake, Tanah Datar, Indonesia, was used as inoculum. The substrate was fed into the reactor through the inside of the filter using a peristaltic pump. Ammonium and nitrite were supplemented to the substrate at a 70-150 mg-N/L concentration and operated at room temperature. The samples were collected once a week. Ammonium and nitrite were measured using the colorimetric method, nitrate using the ultraviolet spectrophotometric method. Performance of nitrogen removal and the growth biofilm in the reactor shown the success of the start of the anammox process. After 140 days of reactor operation, the maximum value of nitrogen removal rate (NRR) was 0.271 kg-N/m3.day at the nitrogen loading rate (NLR) 0.3095 kg-N/m3.day. Ammonium conversion efficiency (ACE) and nitrogen removal efficiency (NRE) during start-up were 97.07% and 91.92%. Red biofilm growth on the filter and the reactor's inner wall, which is characteristic of the anammox bacteria biomass.Keywords: anammox, Indonesia, Koto BaruÃ‚Â Lake, tropicalÃ‚Â Ã‚Â ABSTRAKProses anammox memiliki peran penting dalam penyisihan nitrogen dari perairan secara anaerobik. Sejak ditemukannya anammox pada 1995, belum ada penelitian yang melaporkan keberadaan bakteri anammox dari lingkungan Indonesia. Tujuan dari penelitian ini adalah untuk memulai eksplorasi bakteri anammox dari lingkungan di Indonesia sebagai negara tropis. Eksplorasi dilakukan dengan start-upÃ‚Â proses anammox pada sebuah reaktor kontinu. Reaktor terdiri dari housing filterÃ‚Â yang dilengkapi dengan string wound filter sebagai media lekat untuk biofilm. Lumpur dari Telaga Koto Baru digunakan sebagai inokulum. Substrat dialirkan ke dalam reaktor melalui bagian dalam filter menggunakan pompa peristaltik. Amonium dan nitrit ditambahkan ke substrat dengan konsentrasi 70-150 mg-N/L dan dioperasikan pada suhu kamar. Konsentrasi amonium dan nitrit diukur dengan metode kolorimetri, serta konsentrasi nitrat dianalisis menggunakan metode spektrofotometri UV dengan interval pengukuran sampel setiap 5 hari. Pengamatan penyisihan nitrogen dan pertumbuhan biofilm di reaktor menunjukkan keberhasilan dimulainya proses anammox. Setelah 140 hari operasional reaktor, didapatkan nilai tingkat penyisihan nitrogen Ã‚Â (TPyN) maksimum 0,271 kg-N/m3.hari pada tingkat pemuatan nitrogen (TPN) 0,3095 kg-N/m3.hari. Nilai efisiensi konversi amonium (EKA) dan efisiensi penyisihan nitrogen (EPN) maksimum selama start-up adalah : 97,07% dan 91,92%. Biofilm berwarna merah tumbuh pada filter dan dinding bagian dalam reaktorÃ‚Â yang merupakan karakteristik dari biomasa bakteri anammox.Kata kunci: anammox, Indonesia, Telaga Koto Baru, tropis